ASURANSI KREDIT DALAM HUBUNGANNYA DENGAN PERJANJIAN KREDIT DI PT BANK DANAMON TBK CABANG BANJARMASIN - , Holy Christian Asmin ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The goal of this research is to know and to analyze legal issues arising from Loan Insurance in relation with Loan Agrement and the realization of insurance claims in connection with Loan Agreement at PT Bank Danamon Tbk Banjarmasin Branch Office. The benefits of this research are to provide useful idea for the development of legal science in the field of banking and insurance and also beneficial for developing regulation and policy in the sector of loan insurance. This research applies normative legal method combined with empirical legal method. Legal resources used are primary, secondary dan tertiary legal resources. Besides, primary data is obtained through interview. This research is also based on case study. This research is descriptive analytical, and the analysis is conducted by applying qualitative method and the analysis applies inductive and deductive reasoning. The results of the research shows that there are problems arising from the Loan Insurance in connection with Loan Agreement at PT Bank Danamon Tbk Banjarmasin Branch Office, namely, when the coverage applications are filed the insured does not deal directly with the insurer but through the bank. The insurance company as the insurer is determined by the bank. Insurance policy is made in a form of standard contract. There is double insurance in loan insurance where for the loan awarded it is compulsary to be covered by general insurance in this case fire insurance for the object of the collateral and life insurance for the soal of the insured (debtor). The policy of both life insurance and general insurance made for the loan insurance contain a lot of exception clauses. There are problems in relation with realization of claim of loan insurance at PT Bank Danamon Tbk Banjarmasin Branch Office, seen from the perspective of consumerâs protection, namely, there are claims rejected with the reason that the insured has violated the principle of good faith (Article 251 Commercial Code). From the perspective of Act Number 8 of year 1999 concerning Consumerâs Protection, in the implementation of this loan insurance there are infringements whic disadvantage the insured. The model of liability applied for loan insurance is still based on coventional one, namely liability based on fault.